Preparation of copper-graphene layered composites by spark plasma sintering. Issue 14 (22nd September 2018) - Chen, Xiaohong; Liu, Pengzhong; Liu, Ping; Chen, Haohan
ABSTRACT: In situ chemical vapour deposition-based graphene growth was designed with copper foil as a substrate and used to prepare copper matrix-graphene layered composites by spark plasma sintering. Mechanical properties and corrosion resistance of layered composites were greatly improved when sintered at 700°C and 25 kN for 10 min. Composite had 12% higher Vickers hardness and 30% higher tensile strength comparing with pure copper, respectively. The corrosion potential ( V corr ) of the layered composites shifted towards more positive values and the corrosion current ( I corr ) was significantly lower than that of copper. Corrosion inhibition efficiency ( ) was as high as 68.38% and 36.90%, and the corrosion rate (CR) was 0.047 and 0.093 mm year −1 for the parallel sample and vertical sample, respectively.